Mesoporous Li4Ti5O12 hollow spheres with enhanced lithium storage capability - Yu, Le (2014)
Uniform Li4Ti5O12 hollow spheres with mesoporous shells of tuneable thickness have been synthesized by an efficient templating approach. Owing to the unique hollow structure and highly mesoporous framework, these Li4Ti5O12 hollow spheres exhibit remarkable high-rate performance and long-term cycling stability when evaluated as anode materials for lithium-ion batteries.